Delamination control in composite beams using piezoelectric actuators - Iannucci, L; Shaik Dawood, Mohd. Sultan Ibrahim; Greenhalgh, E; Ariffin, A. K. (2009)
Composite materials have poor tolerance to impact loads. They initially absorb impact energy by creating fracture surfaces, such as matrix cracks and delaminations. In the present work, the possibilities of using of piezoelectric materials to control delamination in composite beams, subjected to low velocity impact are investigated.